Epidemiological and Molecular Characteristics of HIV-1 Infection in a Sample of Men Who Have Sex With Men in Brazil: Phylogeography of Major Subtype B and F1 Transmission Clusters - Silva, Ágabo Macêdo da Costa e; Reis, Mônica Nogueira da Guarda; Marinho, Thaís Augusto; Freitas, Nara Rúbia de; Teles, Sheila Araújo; Matos, Márcia Alves Dias de; Carneiro, Megmar Aparecida dos Santos; Bello, Gonzalo; Stefani, Mariane Martins Araújo; Martins, Regina Maria Bringel (Frontiers in Microbiology, 2020)
This study describes human immunodeficiency virus 1 (HIV-1) prevalence, associated factors, viral genetic diversity, transmitted drug resistance (TDR), and acquired drug resistance mutations (DRM) among a population of 522 men who have sex with men (MSM) recruited by the respondent-driven sampling (RDS) method, in Goiânia city, the capital of the State of Goiás, Central-Western Brazil. All serum samples were tested using a four-generation enzyme-linked immunosorbent assay (ELISA), and reactive samples were confirmed by immunoblotting. Plasma RNA or proviral DNA was extracted, and partial polymerase (pol) gene including the protease/reverse transcriptase (PR/RT) region was amplified and sequenced. HIV-1 subtypes were identified by phylogenetic inference and by bootscan analysis. The time and location of the ancestral strains that originated the transmission clusters were estimated by a Bayesian phylogeographic approach. TDR and DRM were identified using the Stanford databases. Overall, HIV-1 prevalence was 17.6% (95% CI: 12.6–23.5). Self-declared black skin color, receptive anal intercourse, sex with drug user partner, and history of sexually transmitted infections were factors associated with HIV-1 infection. Of 105 HIV-1-positive samples, 78 (74.3%) were sequenced and subtyped as B (65.4%), F1 (20.5%), C (3.8%), and BF1 (10.3%). Most HIV-1 subtype B sequences (67%; 34 out of 51) branched within 12 monophyletic clusters of variable sizes, which probably arose in the State of Goiás between the 1980s and 2010s. Most subtype F1 sequences (n = 14, 88%) branched in a single monophyletic cluster that probably arose in Goiás around the late 1990s. Among 78 samples sequenced, three were from patients under antiretroviral therapy (ART); two presented DRM. Among 75 ART-naïve patients, TDR was identified in 13 (17.3%; CI 95%: 9.6–27.8). Resistance mutations to non-nucleoside reverse transcriptase inhibitors (NNRTI) predominated (14.7%), followed by nucleoside reverse transcriptase inhibitor (NRTI) mutations (5.3%) and protease inhibitor (PI) mutations (1.3%). This study shows a high prevalence of HIV-1 associated with sexual risk behaviors, high rate of TDR, and high genetic diversity driven by the local expansion of different subtype B and F1 strains. These findings can contribute to the understanding about the dissemination and epidemiological and molecular characteristics of HIV-1 among the population of MSM living away from the epicenter of epidemics in Brazil.